Alcohol‐related cirrhosis is associated with high coronary artery calcium scores in patients undergoing evaluation for orthotopic liver transplantation. Issue 5 (23rd March 2021) - Benrajab, Karim; Godman, Macy; Emhmed Ali, Saad; Sorrell, Vincent; Salama, Fady; Shah, Malay; Mei, Xiaonan; Dela Cruz, Anna C.; Gedaly, Roberto
Abstract: Background and aims: Coronary artery disease is a major cause of morbidity and mortality in liver transplant patients. Coronary artery calcium (CAC) score has been used to evaluate the risk of CAD in non‐cirrhotic patients. However, its significance in cirrhotic patients is unknown. This study aimed to identify factors associated with elevated CAC scores in patients with end‐stage liver disease undergoing liver transplant evaluation. Methods: We retrospectively reviewed all patients who underwent liver transplantation evaluation and had coronary CT scan between January 2015 and December 2018. Patients with prior history of CAD were excluded. CAC score was calculated based on the method described by Agatston. Results: Sixty‐two patients were included. 37.1% had alcohol‐related liver disease and 27.4% had NASH cirrhosis. Mean CAC score was 261.1 ± SD, 463.84. Alcohol‐related liver disease, male gender, and hypertension were significantly associated with CAC score >100 and only alcohol‐related liver disease was associated with CAC score >300. In logistic regression, patients with alcohol‐related liver disease had more than sixfold increase in risk of having CAC scores >100 and 300 (OR 6.14, and 6.70, respectively). Conclusion: Alcohol‐related liver disease, male gender, and hypertension were significantly associated with an increased CAC score >100. However, alcohol‐related liver disease was the only factor associated with CAC score >300.